A manual for master's thesis preparation (the structure and formatting requirements) - Krasnokutska, N. S.; Nashchekina, O. M.; Prokhorenko, O. V.; Horbunov, M. P. (My University, 2021)
The final step in the graduate program leading to the Master of Management degree is the submission of a Master’s thesis. A Master’s thesis represents a research project carried out by a student under the direction of a faculty member. The academic curriculum allots 450 hours to the thesis preparation, which corresponds to 15 ECTS credits. A thesis should be prepared in accordance with the university’s standards and requirements for a Master’s thesis concerning its structure, contents, volume as well as the manuscript formatting. This manual is complementary to the Guidelines for the Preparation of Master’s Theses and intended to help students pursuing their master’s degree in management within the educational and professional programs “Management of Organizations and Administration” and “Business Administration” prepare the manuscripts of their master’s theses. The manual lays out the requirements for the manuscript structure and provides instructions for the manuscript formatting (font type, font style, font size, spacing etc.). The manual is based on two standards developed at National technical university “Kharkiv polytechnic institute”: СТЗВО-ХПІ-2.01-2018 і СТЗВО-ХПІ-3.01-2018. It is not meant to be an exhaustive guide for the thesis manuscript formatting but it covers the most important issues and provides examples of the formatting of structural elements of the manuscript. The students should submit both an electronic copy of their theses and a hard copy properly bound. It is the responsibility of the student to make sure that the thesis meets the formatting requirements described in this manual. Before submitting their Master’s theses to the department, students should contact the faculty member responsible for checking the manuscripts for the compliance with the structure and formatting requirements and get his/her approval (signature on the title page).
Keywords: abstract; introduction; references; title page; table of contents; conclusions